Frequency and Predictors of Radial Artery Occlusion after Coronary Procedure through Transradial Approach: A Vascular Doppler-guided Study (Bangladesh Heart Journal, 2019)
Background: Although transradial approach (TRA) has better outcome and reduced vascular complications, radial artery occlusion (RAO) is now a major concern as it limits future radial artery use for further TRA, for use as a conduit during CABG, for invasive hemodynamic monitoring and for creation of arteriovenous fistula for hemodialysis in CKD patients. Vascular doppler study is the most accurate method for evaluation of RAO and yet this is not practiced in our population.Objectives: To detect the frequency and identify the predictors of RAO after coronary procedure through TRA. Methods: This cross-sectional analytical study was done in the department of cardiology, NICVD from July-2015 to June- 2016 by including a total 125 patients undergoing coronary procedures (CAG and/or PCI) through TRA. Vascular doppler study of the radial artery were performed before and one day after the procedure. RAO was defined as an absence of antegrade flow and monophasic flow on doppler study. Univariate and multivariate logistic regression analysis were done to evaluate the predictors of RAO.Results: On the day after the procedure, radial artery vascular doppler examination revealed RAO in 12 (09.6%) patients. On univariate analysis female gender (p= 0.038), diabetes mellitus (p= 0.024), prolonged hemostatic compression for more than 02 hours after sheath removal (p= 0.003) were identified as predictors of RAO. Interestingly hypertension, low BMI, smaller radial artery diameter and use of reprocessed sheath were not identified as predictors of RAO. On multivariate analysis diabetes mellitus (p= 0.016), prolonged hemostatic compression for more than 02 hours after sheath removal (p= 0.004) were found as independent predictors for RAO.Conclusion: Frequency of RAO was 09.6% after coronary procedure through TRA. Diabetes mellitus and hemostatic compression after sheath removal for more than two hours were identified as independent predictors of RAO. Strategies should be taken from patient selection for TRA to end of hemostatic compression removal to prevent RAO.Bangladesh Heart Journal 2019; 34(2) : 111-117